Photogrammetric Analysis of Nasolabial Angle and Mentolabial Angle norm in Malaysian Adults (Bangladesh Journal of Medical Science, 2013)
Introduction: While measurement of nasolabial angle and mentolabial angle is an important clinical examination in pre-orthognathic surgery assessment, data on non-western population is limited. This study was therefore conducted to determine the range of nasolabial angle and mentolabial angle in normal Malaysian adult with comparison of males and females. Materials and Methods: A total of 50 Class I males and 52 Class I females aged 19-30 years from three main ethnic groups were randomly selected from dental students, medical students and staffs in dental clinic of Hospital Universiti Sains Malaysia (HUSM). The photographic set-up consisted of a 50mm Nikon DAT camera held in position by a tripod. The photos taken in JPEG format were digitalized and analysed using ProVixwin software. Independent t-test was used to compare any possible gender difference in nasolabial and mentolabial angles. Results: The mean of nasolabial angle and mentolabial angle for male was 92.99? and 130.44? whereas for females it was 95.04? and 130.73? respectively. Gender differences were found to be insignificant for both nasolabial angle and mentolabial angle. Conclusion: Despite having great variation in our population, the nasolabial angle and mentolabial angle are gender independent. Bangladesh Journal of Medical Science Vol. 12 No. 02 April13 Page 209-214 DOI: http://dx.doi.org/10.3329/bjms.v12i2.14951